2018
DOI: 10.1002/term.2736
|View full text |Cite
|
Sign up to set email alerts
|

Developing a high-throughput platform to direct adipogenic and osteogenic differentiation in adipose-derived stem cells

Abstract: The popular reductionist approach towards stem cell differentiation has identified an array of factors that can induce lineage-specific differentiation. Whether these variables direct differentiation in a multivariable setting in the same way as a single-variable setting is a question of interest. Polyacrylamide hydrogels of specific stiffness were microcontact printed with fibronectin in specific shapes and sizes to construct 54 different extracellular matrix types of defined stiffness, shape, and area. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
(41 reference statements)
1
10
0
Order By: Relevance
“…2,31 Both YAP and MRTFa have been shown to translocate to the nucleus as 2D stiffness increases. 2,11,14 Intriguingly, recent studies have found the YAP nuclear localization trend to be reversed in 3D. 13 In this study, Lamin A was found to decrease in intensity as ECM stiffness increased (Figure 2C,D), reversing the trend previously seen in 2D.…”
Section: ■ Results and Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…2,31 Both YAP and MRTFa have been shown to translocate to the nucleus as 2D stiffness increases. 2,11,14 Intriguingly, recent studies have found the YAP nuclear localization trend to be reversed in 3D. 13 In this study, Lamin A was found to decrease in intensity as ECM stiffness increased (Figure 2C,D), reversing the trend previously seen in 2D.…”
Section: ■ Results and Discussionsupporting
confidence: 68%
“…9 For example, in two-dimensional (2D) cell culture platforms, stem cells differentiate into neurogenic, adipogenic, myogenic, and osteogenic lineages when cultured at the lineagespecific stiffness of native tissues. 1,10,11 Other behaviors such as cell migration and proliferation are also shown to be regulated by ECM stiffness. 2,12 It is crucial to note that the vast majority of our understanding of mechanotransduction and the ECM is derived from studies using elastic 2D culture systems with defined stiffnesses.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Different methods have been developed to deposit these adhesion molecules into a precise pattern. These include stamping or transfer techniques, such as microcontact printing (Major and Choi, 2018), in situ polymerisation (Rape et al, 2011;Vignaud et al, 2014), photolithography and pattern lift-off (Moeller et al, 2018;Sorribas et al, 2002), as well as photochemical patterning such as deep UV activation (Tseng et al, 2011). Moreover, these techniques can be readily applied to hydrogels with different stiffness to combine both surface patterning and substrate stiffness.…”
Section: Surface Patterning and Nanotopographymentioning
confidence: 99%
“…For example, a soft matrix (<1 kPa) promoted neurogenic differentiation whereas a stiff matrix (>25 kPa) promoted osteogenic differentiation. It has been shown that similar outcomes can be achieved by controlling cell shape (McBeath et al, 2004; Kilian et al, 2010; Major and Choi, 2018), whereby increasing cell size promoted osteogenic differentiation and smaller cell size promoted adipogenic differentiation. Stiffness-mediated and shape-mediated changes to cell behavior are believed to both be a consequence of traction force generation, as traction forces can be controlled through both substrate stiffness and cell shape (Califano and Reinhart-King, 2010; Rape et al, 2011).…”
Section: Foundations Of Mechanobiologymentioning
confidence: 90%
“…Spatial patterning of hydrogels can also involve controlling the area available for cells to grow. In the past, this has involved microcontact stamping, to control the spatial distribution of ligands across the substrate (Engler et al, 2004) or microcontact printing, to control the physical area available for cell adhesion (McBeath et al, 2004; Kilian et al, 2010; Major and Choi, 2018). Typically, microcontact printing involves fabricating PDMS stamps that are used to define an area where an ECM protein, such as fibronectin, could be applied allowing cells to adhere to the area marked by the PDMS stamp, but not elsewhere.…”
Section: Emerging Materials and Methods For Understanding Cardiac Mecmentioning
confidence: 99%